2015
DOI: 10.1038/npp.2015.188
|View full text |Cite
|
Sign up to set email alerts
|

Not All Antidepressants Are Created Equal: Differential Effects of Monoamine Uptake Inhibitors on Effort-Related Choice Behavior

Abstract: Motivated behavior can be characterized by behavioral activation and high work output. Moreover, people with depression and other disorders show effort-related motivational symptoms, such as anergia, psychomotor retardation, and fatigue. Effort-based decision making is studied using tasks offering choices between high effort options leading to highly valued reinforcers vs low effort/low reward options, and such tasks could be useful as animal models of motivational symptoms. In the present studies the effort-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
75
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 53 publications
8
75
1
Order By: Relevance
“…Indeed, we have previously found that, while the Q175 HD mouse model employed in the current study exhibits diminished motivation, they do not display behaviors characteristic of depression [20]. In addition, antidepressant treatment may be problematic for apathy in HD because common antidepressants can suppress motivation by altering dopamine input to the NAc [56,57]. Moreover, the only FDAapproved treatment specifically for HD is TBZ, which reversibly inhibits the vesicular monoamine transporter-2 (VMAT-2) to suppress dopamine release [58].…”
Section: Discussionmentioning
confidence: 71%
“…Indeed, we have previously found that, while the Q175 HD mouse model employed in the current study exhibits diminished motivation, they do not display behaviors characteristic of depression [20]. In addition, antidepressant treatment may be problematic for apathy in HD because common antidepressants can suppress motivation by altering dopamine input to the NAc [56,57]. Moreover, the only FDAapproved treatment specifically for HD is TBZ, which reversibly inhibits the vesicular monoamine transporter-2 (VMAT-2) to suppress dopamine release [58].…”
Section: Discussionmentioning
confidence: 71%
“…Diverse tasks have been used in rodents for evaluating behavioral activation and effort-related decision making, including tasks that give animals the option of vigorously working (lever pressing or climbing a barrier) to obtain access to more highly valued reinforcers vs. approaching and consuming a less preferred reinforcer (Cousins et al, 1994;Salamone and Correa, 2002;Salamone et al, 2016;Mott et al, 2009;Mai et al, 2012;Pardo et al, 2012Pardo et al, , 2015Randall et al, 2012;Sommer et al, 2014;Yohn et al, 2015aYohn et al, , 2016bCorrea et al, 2018;SanMiguel et al, 2019). In these tasks, conditions that alter DA transmission, such as administration of DA antagonists or tetrabenazine (TBZ), can alter behavioral activation and reduce selection of high-effort choices in rats (Nunes et al, 2013;Randall et al, 2014;Hosking et al, 2015;Pardo et al, 2015;Yohn et al, 2015aYohn et al, , 2016aContreras-Mora et al, 2018;Rotolo et al, 2019). TBZ acts by inhibiting the vesicular monoamine transporter-type 2 (VMAT-2), which leads to a blockade of vesicular storage and a depletion of monoamines, with its greatest effects at low doses being on striatal DA in rats and mice (Pettibone et al, 1984;Nunes et al, 2013;López-Cruz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies also reported that SSRI treatments increase motivation or at least the sensitivity to reward (Tang et al, 2009; Stoy et al, 2012; Yuen et al, 2014). The related animal literature is also contradictory: some studies on cost/benefit trade-off showed reduced effort expenditure with SSRIs (Yohn et al, 2016) or no effect with serotonin blockers (Denk et al, 2005), while other studies reported increased motor activity induced by SSRI (Weber et al, 2009) or optogenetic stimulation of the dorsal raphe nucleus (Warden et al, 2012). …”
Section: Introductionmentioning
confidence: 99%